Determination of Slaughter and Carcass Traits in Male Turkish Anatolian Buffaloes at Different Slaughter Weights - Ulutaş, Z.; Şahin, A.; Aksoy, Y.; Uğurlutepe, E. (TÜBİTAK, 2021)
Nowadays, deficits in red meat resources in Turkey are caused by the import of red meat from different countries. Anatolian buffaloes used in this research are a species that can contribute to red meat production in Turkey. This study was performed to determine the slaughter and carcass traits of Anatolian buffaloes at different slaughter weights. Twenty weaned male Anatolian buffalo calves of about 5 months old, at an average live weight of 100 kg, were used as the animal specimen in the present study. The calves were fed with 30:70 roughage (alfalfa hay = 18.07% crude protein, 2186.90 kcal kg-1 metabolic energy DM): concentrate feed (cattle fattening feed = 16.40% crude protein, 2696.94 kcal kg-1 metabolic energy DM). The calves were randomly distributed into 4 different slaughter weight (SW) groups of GI (200 kg; n = 5), GII (250 kg; n = 5), GIII (300 kg; n = 5), and GIV (350 kg; n = 5). The results showed that hot and cold carcass ratios (P < 0.01) and carcass chilling loss increased with increasing slaughter weights. Except for head, feet, and kidney weight, the differences in all of the other organ weights of the SW groups were not statistically significant. The differences in all of the investigated carcass measurements of the SW groups were detected to be significant (P < 0.05). Although total carcass conformation index values increased with increasing slaughter weights, only the differences in the carcass compactness values of the SW groups were statistically significant (P < 0.001). Except for chunk, short loin, sirloin, rump, and flank ratios, the differences in all of the other carcass section ratios of the SW groups were statistically significant (P < 0.05). © TÜBİTAK
Keywords: Anatolian Buffalo; Carcass Measurement; Carcass Traits; Slaughter Weight